Sequence analysis of alphavirus pathogenesis - Logue, Christopher H. (Trinity College (Dublin, Ireland). Department of Microbiology, 2006)
This investigation involved the sequencing and characterisation of Chikungunya virus (CHIKV), a positive-stranded RNA virus with a genome spanning 11.8 kb. The prototype strain of CHIKV, termed Ross was used. This is the first complete genome of CHIKV to be sequenced and submitted to Genbank (Accession No. AF490259). CHIKV was analysed in relation to six other geographically distinct CHIKV strains and Semliki Forest virus which is well characterised in our laboratory. This is the first report of CHIKV being characterised both in vitro and in vivo. The rate of RNA production, rate of infection and cell tropism were investigated in vitro, while the multiplication of virus in the brains of infected Balb/c mice, mortality rates, and the neuropathology caused were studied in vivo. To fully ascertain the functions of various CHIKV genes and their possible roles in causing disease, the construction of a CHIKV full-length cDNA clone was subsequently carried out.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin